2009
DOI: 10.1590/s0004-28032009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Recalled and recorded bowel habits confirm early onset and high frequency of constipation in day-care nursery children

Abstract: -Context -Mothers recall early-onset constipation in children attending gastroenterology clinics. Objectives -To study the bowel habit of young children in the community to determine, first, whether early-onset constipation is confirmed in this setting and, second, the agreement between recalled and recorded bowel habit. Methods -Defecation data of 57 children aged 6.0-40.7 mo were obtained by maternal recall (questionnaire on predominant stool characteristics) and by record (1,934 defecations registered prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The relatively high convergence between the normative diary coding scheme and the parent‐report questionnaire also suggests that parents are assessing their child’s symptoms as compared with general norms for pain and stooling, rather than assessing symptoms within the child over time. This same higher convergence between parent recall and diary coding of normative definitions of constipation, but not by intra‐individual comparisons, was found in a recent study of infant stooling 21 . If assessing stooling changes within the child over time is important, parents will need that specific directive.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The relatively high convergence between the normative diary coding scheme and the parent‐report questionnaire also suggests that parents are assessing their child’s symptoms as compared with general norms for pain and stooling, rather than assessing symptoms within the child over time. This same higher convergence between parent recall and diary coding of normative definitions of constipation, but not by intra‐individual comparisons, was found in a recent study of infant stooling 21 . If assessing stooling changes within the child over time is important, parents will need that specific directive.…”
Section: Discussionmentioning
confidence: 69%
“…This same higher convergence between parent recall and diary coding of normative definitions of constipation, but not by intra-individual comparisons, was found in a recent study of infant stooling. 21 If assessing stooling changes within the child over time is important, parents will need that specific directive.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazilian community studies, 21% to 22% of infants already present constipation (17,26) . Also, 1/3 to 2/3 of mothers of children attended with constipation refer its onset in the first year of life (16,(27)(28)(29)(30) , and these data are trustable, since in a similar population it has been shown that recalled data were similar to recorded data (31) . Van Tilburg et al (10) also showed this similarity, but agreement between daily dairies and the Rome III questionnaire was poor.…”
Section: Timing Of Diagnosismentioning
confidence: 86%